Getting to the heart of intracellular glucocorticoid regeneration: 11β-HSD1 in the myocardium. (January 2017) - Gray, Gillian A; White, Christopher I; Castellan, Raphael F P; McSweeney, Sara J; Chapman, Karen E
Abstract : Corticosteroids influence the development and function of the heart and its response to injury and pressure overload via actions on glucocorticoid (GR) and mineralocorticoid (MR) receptors. Systemic corticosteroid concentration depends largely on the activity of the hypothalamic–pituitary–adrenal (HPA) axis, but glucocorticoid can also be regenerated from intrinsically inert metabolites by the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), selectively increasing glucocorticoid levels within cells and tissues. Extensive studies have revealed the roles for glucocorticoid regeneration by 11β-HSD1 in liver, adipose, brain and other tissues, but until recently, there has been little focus on the heart. This article reviews the evidence for glucocorticoid metabolism by 11β-HSD1 in the heart and for a role of 11β-HSD1 activity in determining the myocardial growth and physiological function. We also consider the potential of 11β-HSD1 as a therapeutic target to enhance repair after myocardial infarction and to prevent the development of cardiac remodelling and heart failure.